2007
DOI: 10.1111/j.1475-4983.2007.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

PTERYGOTUS ANGLICUS AGASSIZ (CHELICERATA: EURYPTERIDA) FROM ATHOLVILLE, LOWER DEVONIAN CAMPBELLTON FORMATION, NEW BRUNSWICK, CANADA

Abstract: Specimens of the large eurypterid Pterygotus from the Early Devonian Campbellton Formation outcropping at Atholville, New Brunswick, are identified as Pterygotus anglicus Agassiz. The locality, in the Atholville beds near the western end of the Campbellton Formation exposure, is best known for its vertebrate fauna of ostracoderms, arthrodires, acanthodians and chondrichthyans, first described in 1881. Although a significant series of pterygotid fossils was acquired by the Natural History Museum, London, in 189… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 42 publications
(88 reference statements)
1
39
0
Order By: Relevance
“…Parahughmilleria that was probably part of an estuarine assemblage. Miller (2007a) discussed the Campbellton Formation pterygotid fauna as inhabiting estuarine or lagoonal paleoenvironments. Sizes of individuals suggested that juveniles and adults comprised the assemblage.…”
Section: Discussionmentioning
confidence: 99%
“…Parahughmilleria that was probably part of an estuarine assemblage. Miller (2007a) discussed the Campbellton Formation pterygotid fauna as inhabiting estuarine or lagoonal paleoenvironments. Sizes of individuals suggested that juveniles and adults comprised the assemblage.…”
Section: Discussionmentioning
confidence: 99%
“…Pterygotus anglicus from the Atholville locality (Miller 2007) occurs higher in the section in a relatively unfossiliferous mudstone (Fig. 2), with only occasional to rare plant fragments and few ostracods.…”
Section: Resultsmentioning
confidence: 99%
“…A lagoon or estuary environment is likely represented (Miller 2007) since rare prasinophyte algae (tasmanitids) from the upper part of the section at Atholville (Fig. 2) indicate a marine connection (Blieck and Cloutier 2000).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations